Community Empowerment Based on Potential of Marine Resources in Tanjung Tiram Village, South Konawe District, Southeast Sulawesi - . Asriyana; Nur Irawati; . Haslianti (Institut Pertanian Bogor, 2018)
The village of Tanjung Tiram is a coastal area with considerable fishery resource potential. Community services activity through Program of student study service and community empowerment (KKN-PPM) program for 45 days from May 20th–July 16th 2017. The activity aims to provide knowledge and empower the community of Tanjung Tiram Village through the enhancement of value added potential of aquatic resources (seaweed and fish). The activity was conducted through training to make various processed food products based on seaweed and fish so that economic value of fishery products increases. In addition there are also alternative jobs for fishermen/communities who have been doing the utilization of natural resources that damage (no eco-friendly). The result that had been obtained in this activity was the community understand the method of processing and packaging of processed seaweed and fish products, and they have succeeded in making processed products in packaging that is ready to be marketed.